Perodua Manufacturing Training System : Visual Manual - Nurul Izzati, Saief Al-Aman (Universiti Malaysia Sarawak (UNIMAS), 2019)
The use of teaching aids in learning and teaching is important in ensuring an engaging, interactive and also effective environment. With the development of technologies these days, modern ways of teaching such as implementation of e-learning, courseware, slideshows and visual aid are being used widely in various field including industrial. This project introduced a teaching courseware namely Visual Manual that is used by trainers of various Shops from Developmental and Dojo Education Perodua Manufacturing Sdn. Bhd. during training sessions. The content in Visual Manual consists of the basic processes, safety, awareness and standards required in manufacturing processes. However, as time passes by along with the growth of new technologies, Visual Manual has a downside as it is outdated and obsolete. Due to this issue, a demand to present a Visual Manual that is updatable, operable and stable is required by the trainers in order to ease their teaching processes. The features that is implemented in this project consists of managing courses, display training progress, generate training session report and translation option for the training courses. The project makes use web-based programming language including HTML, JavaScript and PHP by the application of Rapid Prototyping for ISD Model as its methodology. Visual Manual is expected to have improvements that is beneficial to the users and also will affect the learning and teaching process efficiently, and in order to ensure the objective is achieved, development process is being done, followed by testing that received mixed reaction from its users such as intrigued, confused and also glad.